Terrorism an investigator's handbook - Dyson, William E. (Anderson Pub., 2012)
Introduces the reader to the field of terrorism investigation. Describing how terrorists operate and how they differ from other criminals, this title provides an outline of how terrorism investigations should be conducted. By helping investigators to develop skills and knowledge, it lets them to prepare prosecutable cases against terrorists.